Zeylu mir’ati’z-zaman. Cild I : min vekai’i seneti H. 654 ila esnai seneti H. 662 = Dhail Miratu’z-zaman or supplement to the mirror of the age. Vol. I : 654-662 A. H./1256-1263 A. D. - el-Yunini, Kutbüddin Ebi’l-Feth Musa b. Muhammed b. Ahmed b. Kutbüddin el-Balebekki el-Hanbeli, ?-1326 (Haydarabad)
[25], 557, [6] s.